Tasks and Powers of Criminal Justice Officers in the Saudi System: A Comparative Study with Sudanese Law - Hamid, Abusalif Adam Mustafa (Journal of Ecohumanism, 2025)
Nearly all legal systems in developed nations concur on enshrining rights and freedoms within their constitutions. These rights and freedoms have further been incorporated into international and regional covenants. Among the most crucial of these are the right to personal liberty, the right to privacy, and the freedom of movement and residence. Both the Basic Law of Governance in the Kingdom of Saudi Arabia and the Constitutional Document in Sudan recognize these rights and provide constitutional protections. However, there is a critical need to balance the rights and interests of the accused with the interests and right of society to security. This requires ensuring that criminals do not escape punishment if due process of apprehension and investigation is not followed, even if such processes infringe on personal liberties. Equally important is the need to investigate criminal evidence promptly, as some evidence cannot be retrieved during the trial and must be collected contemporaneously with the crime. This necessitates some infringement on these rights to prevent the escape of the accused or their tampering with evidence, which could lead to impunity and a failure of justice. Perhaps the first instance of such infringement occurs through the procedures and powers granted to criminal justice officers, which this research will examine. This study comprises two main chapters. The first chapter addresses criminal procedure and investigation, including the definition of criminal justice officers and their powers, the structure of the law enforcement apparatus, and the required qualities of these officers. The second chapter will cover the process of filing a criminal lawsuit and the tasks and powers of law enforcement officers. The research will conclude with a summary of findings and recommendations.